'The goal is not necessarily to sit at the table'—Resisting autocratic legalism in Hungarian academia. (4th December 2020) - Labanino, Rafael; Dobbins, Michael
Abstract: The article analyses the strategies of Hungarian higher education interest organisations against the encroachments on academic freedom by Viktor Orbán's governments. We contrast the 2012–2013 and 2017–2019 protest waves and find that innovations in strategy came from new organisations in both periods, whereas established ones were rather passive or opted for the status quo. However, in the second period, new actors consciously declined to pursue wider systemic goals and aimed at building up formal organisations instead of loose, movement‐like networks. The focus on keeping a unified front and interest representation on the workplace level did not change the overall outcome. Just like during the first period, the government was able to reach its goals without major concessions. Nevertheless, during the second protest wave the government was unable to divide and pacify its opponents, which stripped it of its legalistic strategy and revealed its authoritarianism. Kivonat: Ez a cikk a legfontosabb magyar felsőoktatási érdekszervezetek, az Orbán‐kormányok egyetemi autonómiát korlátozó lépései elleni stratégiáit elemzi. A cikk a 2012–2013‐as és a 2017–2019‐es tiltakozási hullámok összehasonlító elemzése alapján megállapítja, hogy a stratégiai innováció mindkét esetben az új szereplőktől érkezett, míg a nagy, hagyományos érdekszervezetek vagy inkább passzívak voltak, vagy végül a kormánnyal való status quot választották. A második tiltakozási hullám során azonban az új szereplők tudatosan lemondtak a tágabb, rendszerszintű célok hangsúlyozásáról és formális szervezeti struktúra felépítésére törekedtek a laza, hálózatszerű mozgalmi forma helyett. A kormánnyal szembeni egységre és a munkahelyi érdekvédelemre való törekvés nem volt képes változtatni a végeredményen. Csakúgy, mint az előző tiltakozási hullám során, a kormány kevés engedménnyel elérte célját. Mindennek ellenére a második tiltakozási hullám során a kormány nem tudta megtörni az ellenállás egységét, ami megfosztotta a kormányt legalista stratégiájától és leleplezte tekintélyelvűségét.